(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Job satisfaction is a cognitive, affective and evaluative reaction towards a job. It is closely linked to an individual’s behaviour in the work place. Health Care Professionals of Combined Military Hospitalsface diverse stressful situations while accomplishing their professional commitments. They often concede job satisfaction as a stressor stemming to their work place. Objectives: To findout the Job Satisfaction level among the Healthcare Professionals of CMH in Bangladesh. Materials and Methods: A total of 574 respondents were selected from five CMHs using simple random sampling considering doctors, nurses, paramedic medical assistants and technologists as the study population. The level of job satisfaction was elucidated by certain parameters and occupational stress was measured by Health Professions Stress Inventory. Results: A high proportion of respondents were found to be satisfied or highly satisfied in regards to work prospects (61.4%), people they worked with (86.5%), physical working conditions (79.4%), the way their department was run (80.7%), the way their abilities were used (78.2%) and their interest and skill involved in their job (77.4%). On the contrary, a marginal majority (56.7%) were dissatisfied in regards to their salary. 32.4% were found to be not at all worried about losing their job and more than a half (60.8%) mentioned that they feel fairly secured financially for the next 10 years.A significant relationship has been found between job satisfaction and stress (p<0.05). Conclusion: Professional uniqueness contributes significantly to job satisfaction. Particular improvements in working life can be materialized through scientific planning, maintenance and optimization, valuation of human resources and necessary organizational support. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 164-168